Highly Selective Precipitation of Platinum(IV) from HCl Solutions Using m-Phenylenediamine Utilizing Difference in Stability of Ionic Crystals - Kazuya Matsumoto; Yuki Hata; Hiroshi Katagiri; Mitsutoshi Jikei (Metals)
The development of a selective separation and recovery method for platinum-group metals (PGMs) is in high demand to establish efficient and practical recycling technologies for different secondary materials such as industrial automobile catalysts. In this study, the highly selective precipitation of Pt(IV) from hydrochloric acid (HCl) solutions containing Pd(II), Pt(IV), and Rh(III) was successfully achieved using m-phenylenediamine dihydrochloride (MPDA) as a precipitant. Pt(IV) selectivity was observed at HCl concentrations higher than 7 M, whereas the co-precipitation of Rh(III) could not be suppressed using 3–7 M HCl solutions. Successful recovery of Pt(IV)-containing precipitates with high Pt yield (94.6%) and Pt purity (98.5%) was also achieved using an actual catalyst leaching solution with a complex composition containing PGMs, base metals, and rare metals. Structural analyses revealed that the Pt(IV)-containing precipitate forms ionic crystals composed of [PtCl6]2−/protonated m-phenylenediamine (MPDA-2H+) in a 1:1 ratio. The high stability and insolubility of the Pt(IV)-containing ionic crystals, owing to their highly packed structure, resulted in the highly selective precipitation of Pt(IV) at high HCl concentrations.